East Asian international doctoral students’ role identity development in the United States: A collaborative autoethnography - Wu, Qiling; Ji, Hyangeun; Park, Yuhyun; Kim, Sori; Yang, Jiayu; Wang, Lei (Journal of International Students, 2025)
The U.S. attracts a significant number of international doctoral students each year. As these students navigate cultural and academic systems, understanding their unique experiences and challenges becomes crucial. This study explores the intricate nuances of motivation and identity negotiation in the lived experiences of six East Asian international doctoral students in the U.S. using collaborative autoethnography. We examined how role identities explain our experiences by employing the Dynamic Systems Model of Role Identity framework. Our reflections revealed (1) the salience of role identity components and structural relations and the impact of other role identities on resolving tensions; (2) the development of our researcher and teacher role identities within doctoral student role identity; and (3) resilience as both a cultural disposition and a dynamic process that evolves through the constant negotiation and renegotiation of our identities.